Perception of Students from the Faculty of Sports Science about Badminton as a Favorite Sport: A Case Study at State University of Medan. - Hudani, Ammalina; Sihite, Kristini; Silaban, Daniel (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Objective.The point of this study is to find out what students in the Faculty of Sports Science at Universitas Negeri Medan (UNIMED) think about badminton being their favorite sport. Materials and Methods. Findings were gathered using a qualitative method, with 30 current badminton-playing students taking part in interviews, participatory observations, and documentation studies. The results show that national successes in badminton at the world level for Indonesia, like those of famous athletes Susi Susanti and Taufik Hidayat, are what really get students interested in the sport. Students are also interested because playing badminton is a family and community tradition that goes back to early childhood, and there are tools on campus that make it easy for students to do so. Students also see badminton as a good way to make a living, either as a player or in sports management. Students have positive views about badminton because of the social setting on campus, which includes support from peers and teachers. This study gives us information about what makes students interested in badminton, which can be used to help plans sports programs at colleges and universities. One of the best things about this study is that it focused on a clear group of students who were regularly playing badminton. This allowed for more in-depth qualitative insights into how they felt. Using more than one way to collect data, like talks, observations, and written records, makes the data more reliable and complete. One problem with the study, though, is that it only had 30 subjects, which may not fully reflect the views of young people in general. Also, the study only looked at Universitas Negeri Medan. This means that the results might not apply to other schools that have different sports cultures or equipment. For future research, it is suggested that the sample size be increased to include students from more than one university. This would give researchers a more complete picture of why college students like badminton. Researchers could also look at the points of view of students who play other sports to make comparisons and learn more about how people in classroom settings generally feel about sports. Results.The results of this study show how important it is for academic programs to support sports like badminton because they help students grow personally and professionally and could lead to jobs in athletics, coaching, and sports management. Conclusins. This study shows that the social setting, Indonesia's badminton achievements, culture, and the availability of facilities all play a big role in why students at the Faculty of Sports Science, Universitas Negeri Medan (UNIMED) think badminton is their favorite sport. Encouragement from classmates, teachers, and parents, along with the setting up of events, are also big parts of getting students to participate. Overall, badminton is seen not only as a sport but also as a way to improve social skills, learn new things about yourself, and look into job prospects. These results can be used to help create sports programs in colleges and universities that will get more students to play badminton and other sports.